Effects of neural progenitor cells on post-stroke neurological impairment—a detailed and comprehensive analysis of behavioral tests - Doeppner, Thorsten R.; Kaltwasser, Britta; Bähr, Mathias; Hermann, Dirk M. (Frontiers in Cellular Neuroscience, 2014)
Systemic transplantation of neural progenitor cells (NPCs) in rodents reduces functional impairment after cerebral ischemia. In light of upcoming stroke trials regarding safety and feasibility of NPC transplantation, experimental studies have to successfully analyze the extent of NPC-induced neurorestoration on the functional level. However, appropriate behavioral tests for analysis of post-stroke motor coordination deficits and cognitive impairment after NPC grafting are not fully established. We therefore exposed male C57BL6 mice to either 45 min (mild) or 90 min (severe) of cerebral ischemia, using the thread occlusion model followed by intravenous injection of PBS or NPCs 6 h post-stroke with an observation period of three months. Post-stroke motor coordination was assessed by means of the rota rod, tight rope, corner turn, inclined plane, grip strength, foot fault, adhesive removal, pole test and balance beam test, whereas cognitive impairment was analyzed using the water maze, the open field and the passive avoidance test. Significant motor coordination differences after both mild and severe cerebral ischemia in favor of NPC-treated mice were observed for each motor coordination test except for the inclined plane and the grip strength test, which only showed significant differences after severe cerebral ischemia. Cognitive impairment after mild cerebral ischemia was successfully assessed using the water maze test, the open field and the passive avoidance test. On the contrary, the water maze test was not suitable in the severe cerebral ischemia paradigm, as it too much depends on motor coordination capabilities of test mice. In terms of both reliability and cost-effectiveness considerations, we thus recommend the corner turn, foot fault, balance beam, and open field test, which do not depend on durations of cerebral ischemia.